The Effectiveness of Project-Based Differentiated Learning in Improving Descriptive Writing Skills : A Study of Elementary School Students - Istiqomah, Nur; Apoko, Tri Wintolo (Jurnal Paedagogy, 2025)
This study aims to analyze the effectiveness of implementing project-based differentiated learning in improving elementary school students' descriptive text writing skills. This study used a mixed method with an explanatory sequential design. The participants of the study were 48 fifth grade students at a public elementary school in South Jakarta, who were divided into two groups, namely the experimental and control classes. The instruments used included writing tests, questionnaires, and semi-structured interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data used thematic analysis. The results showed that there was a significant increase in students' descriptive text writing skills in the experimental group. In addition, qualitative results showed that students had positive perceptions of this learning method. This study provides recommendations for elementary school teachers to consider project-based differentiated learning for more effective teaching and contribute to increasing students' motivation and confidence in learning.